Need Analysis on Lexical Units of Reading Material in An ELT Textbook - Ro'ifah; Waode Hamsia (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Learning source is one of essential learning aspects for learning foreign or second language. Using learning sources is hoped to be able to enable learners increase the learners’ language mastery exclusively in terms of vocabulary. The learning sources especially reading materials used in the teaching learning activity must be designed for accomplishing lexical units needed by the learners based on the learning objectives, satisfactory vocabulary in the relations of number and range. This research aims to evaluate whether the learning materials especially reading materials of the textbook, Developing English Competencies 3 fulfill can the learners’ need on vocabulary acquisition. A descriptive quantitative study with the specific linguistic field, corpus was designed for this research. RANGE and FREQUENCY, a computational device as instruments created by Nation in 2001 and then, advanced by Heatley, Nation, and Coxhead in 2002 was used to count the lexical units. By comparing to general frequency list, Michael West’s GSL (1953), it was found that the book was accomplishing the lexical needed by the learners of high school level in vocabulary quantity and range in the reading materials because of the amount of 5,064 tokens and 1,434 types only with the unfair distribution based on Nation ‘s three ranges. In brief, the book looks like very distant from the frame of the learners’ needs. In addition, it is restricted to propose the possible comprehensive situations where the learners can present in the daily communication.